2001
DOI: 10.1096/fj.01-0487fje
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing of CRH‐R1 receptors in human and mouse skin: identification of new variants and their differential expression

Abstract: We identified four new isoforms of human CRH-R1 (e-h) and three of mouse (mCRH-R1c, e, and f). In all new forms exon 6 was missing. Human CRH-R1e was characterized by the deletion of exons 3 and 4; exon 12 from CRH-R1f; exon 11, 27 base pairs (bp) of exon 10 and 28 bp of exon 12 from CRH-R1g and CRH-R1h by the addition of a cryptic exon. In mouse CRH-R1c exon 3 was spliced out; in mCRH-R1e exons 3 and 4 and in mCRH-R1f exon 11 were spliced from mRNA. CRH-R1 was expressed in all skin specimens in patterns depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
214
0
3

Year Published

2003
2003
2010
2010

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 170 publications
(224 citation statements)
references
References 49 publications
7
214
0
3
Order By: Relevance
“…All samples were standardized for analysis by the amplification of housekeeping gene GAPDH as described previously [25]. Mouse TPH was amplified by a single PCR, while serotonin AANAT was amplified by nested PCR.…”
Section: Rna Extraction and Cdna Preparationmentioning
confidence: 99%
“…All samples were standardized for analysis by the amplification of housekeeping gene GAPDH as described previously [25]. Mouse TPH was amplified by a single PCR, while serotonin AANAT was amplified by nested PCR.…”
Section: Rna Extraction and Cdna Preparationmentioning
confidence: 99%
“…Thus, it has been reported that activation of protein kinases (PKA and PKC) and environmental insults (UV irradiation) can lead to modulation of CRH-R1 mRNA expression in keratinocytes and melanoma cells [34]. In addition, physiological changes, such as the onset of labour, can alter the relative expression of CRH-R1 variants in the uterus [102].…”
Section: Mechanisms Of Alternative Splicing Of Gpcrsmentioning
confidence: 99%
“…A fascinating example of the importance of splicing in GPCR biology and hormone actions is the CRH-R1 receptor, which orchestrates mammalian responses to stressful stimuli [33]. In humans the CRH-R1 gene spans over 50 kb and contains 14 exons, and at least 14 alternatively spliced mRNAs for CRH-R1 variants have been detected to date [33,34]. The complete gene product incorporating all 14 exons encodes a 444-amino acid GPCR, termed CRH-R1β, which displays weak agonist binding and impaired signalling properties [93][94][95].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CRH-R1 gene expresses multiple subtypes (Ross et al, 1994) (Grammatopoulos et al, 1999) (Pisarchik and Slominski, 2001), which are produced by differential exon splicing. Similar exon rearrangements have been described for the calcitonin and parathyroid hormone/parathyroid hormone-related peptide receptors.…”
Section: Crh Receptorsmentioning
confidence: 99%